2018
DOI: 10.1210/js.2018-00142
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Plasma Glucagon Kinetics in Type 2 Diabetes Mellitus: Comparison of Immunoassay and Mass Spectrometry

Abstract: ContextAccurate glucagon level measurements are necessary for investigation of mechanisms for postprandial hyperglycemia in type 2 diabetes.ObjectiveTo evaluate the accuracy of postprandial glucagon level measurements using a sandwich ELISA vs a recently established liquid chromatography-high resolution mass spectrometry (LC-HRMS) method in type 2 diabetes mellitus.Design and ParticipantsTwenty patients with type 2 diabetes treated with insulin underwent a meal test before and after administration of the dipep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
(24 reference statements)
2
8
0
Order By: Relevance
“…These results indicate that glucagon sandwich ELISA is a simple, effective, and reliable method for clinical examinations that are often conducted in variable conditions. Contrary to the suppression of glucagon secretion by glucose loading, glucagon secretion is enhanced by meal loading in healthy subjects [15,17,29,30] and T2DM patients [18]. We confirmed these opposite plasma dynamics of glucagon in the healthy subjects.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These results indicate that glucagon sandwich ELISA is a simple, effective, and reliable method for clinical examinations that are often conducted in variable conditions. Contrary to the suppression of glucagon secretion by glucose loading, glucagon secretion is enhanced by meal loading in healthy subjects [15,17,29,30] and T2DM patients [18]. We confirmed these opposite plasma dynamics of glucagon in the healthy subjects.…”
Section: Discussionsupporting
confidence: 68%
“…This measurement system enables accurate measurement of plasma glucagon as well as evaluation of the reliability of existing glucagon assays. In a comparative analysis of plasma glucagon measured by sandwich ELISA and LC-HRMS, values determined by the two methods were highly correlated during OGTT and MTT in healthy subjects [17] and during MTT in T2DM patients [18]. Therefore, we consider sandwich ELISA sufficiently reliable to use it to evaluate plasma glucagon levels in T2DM patients as well as in healthy subjects.…”
mentioning
confidence: 99%
“…This result is not surprising because (1) the plasma glucose level improved (with HbA1c being 6.7% [49 mmol/mol]) after 4 weeks of treatment and the glucagon-lowering action of GLP-1 is glucose-dependent [20], and (2) the baseline plasma glucagon level was not elevated in our subjects, while the plasma C-peptide level (representing endogenous insulin secretion) was not low. A recent single-arm study comparing the plasma glucagon level measured by the same LC-HRMS method that we used or by a commercial ELISA kit showed significant reduction of plasma glucagon by the same anagliptin regimen as ours [21]. That study recruited patients on insulin and the baseline plasma C-peptide AUC was lower than in our subjects, while the plasma glucagon AUC was higher.…”
Section: Discussionsupporting
confidence: 48%
“…Holst et al [8] reported that accurate measurements of glucagon could be performed using a sandwich enzyme-linked immunosorbent assay (ELISA) approach. The accuracy of this method was also confirmed by comparing the results with those of LC-HRMS [1]. Currently, sandwich ELISA might be a useful option for measuring glucagon in patients with T2DM [9], but the accuracy of sandwich ELISA in measuring glucagon of HD patients with T2DM remains unclear.…”
Section: Introductionmentioning
confidence: 75%
“…The dynamics of glucagon are receiving considerable attention as a new target in the treatment of diabetes [1,2]. Achieving good glycemic control is important, even in hemodialysis (HD) patients with type 2 diabetes (T2DM).…”
Section: Introductionmentioning
confidence: 99%